Islamic Law, Social Perception, and the Normalization of Premarital Pregnancy in Rural Indonesia - Insan Jaelan; Fatum Abubakar; Abdul Haris Abbas; Nursinita Killian; Ziaulrahman Mushkalamzai (Al-Syakhsiyyah: Journal of Law and Family Studies, 2026)
This study aims to analyze public perceptions of the rising phenomenon of out-of-wedlock pregnancies in Pangeo Village, Morotai Island Regency, and to examine the influence of Islamic legal perspectives on the community’s social constructs. The research focuses on the social impacts of promiscuity and the normalization of premarital pregnancy among adolescents and adult women. The study employs a qualitative, phenomenological approach based on fieldwork. Informants were selected through purposive sampling and included seven members of the Pangeo Village community. Primary data were collected through in-depth interviews and analyzed using Harvey and Smith’s theory of social perception to understand how the community’s social judgments regarding this phenomenon are formed. The results indicate that the community views out-of-wedlock pregnancy as unacceptable behavior, as it is perceived to have negative consequences for the morality and social lives of the younger generation. From an Islamic legal perspective, the validity of a relationship between a man and a woman is only recognized through a marriage that meets Sharia requirements. In contrast, relationships outside of marriage are viewed as contrary to the principles of moral protection and lineage. This study contributes to strengthening Islamic socio-legal studies regarding the relationship between religious norms, social perceptions, and local cultural dynamics in contemporary Muslim societies.